(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The paper is devoted to the issues of state regulation of sustainable development of territories taking into account their spatial differentiation and presents an analysis of the modern state and trends in the level of their development, spatial differentiation, mechanisms, scale, and efficiency of public interaction. The authors prove that social-economic and ecological development of municipal territories is uneven and differentiation by most of the key indicators deepens. State regulation cannot comprehensively improve sustainable development of the Russian municipal territories, taking into account their spatial advantages. The necessity is proved to elaborate theoretical approaches and methodological provisions of the new spatial policy of Russia (intraregional aspect) within the sustainable development paradigm; to search for optimal mechanisms, methods, and forms of the state’s influence on increasing the territories’ sustainability, taking into account their spatial advantages; to identify the spatial carcass of the regional development, including advanced growth nodes and links between them; to plan the advanced development of these “growth territories"; and to elaborate projects for involving the “weak” territories into the “orbit of influence” of these nodes.